Analysis of Chemical Constituents of Volatiles and Petroleum Ether Extract from the Branch of Zanthoxylum bungeanum by GC-MS - Liu, Yuan-Yuan; Shen, Xin; Zhang, Ya; Cao, Wei; Wang, Kai; Xu, Shou-Zhu; Wang, Si-Wang (Asian Journal of Chemistry, 2014)
The essential volatiles were extracted by water steam distillation and the petroleum ether extract was extracted with alcohol and then petroleum ether from the branch of Zanthoxylum bungeanum. The chemical constituents of essential volatiles and petroleum ether extract were analyzed by GC-MS and their relative contents were calculated by area normalization method. 45 peaks were obtained and 34 components were identified from the volatiles and the major components were terpenes, alcohols and fats. As for petroleum ether extract, 60 peaks were obtained and 50 components were identified and the major components were organic acids, esters and alkanes.